ความชุก ปัจจัย และผลกระทบของอาการปวดศีรษะจากไมเกรน ในนิสิตคณะแพทยศาสตร์ มหาวิทยาลัยนเรศวร - วัฒนชีวโนปกรณ์ เศรษฐดา; ตันพรพิทักษ์ ภัทราพร; เล็กพุฒิกานต์ พุธิตา; โภคศิริ ธนกฤต; ศิลกุล ศุภวิชญ์ (Health Science Clinical Research, 2021)
Background : Migraine is one of the most severe headache disorders. The etiology of migraine is remained unknown but believing that migraine’s symptoms cause by several trigger factors such as stress, inadequate sleeping etc. These factors associated with academic learning and daily life of medical students. The migraine’s symptoms also influence academic learning performance in medical students worldwide. Objective : To survey the prevalence and general characteristics of migraine in medical students of Naresuan University. To study trigger factors and relieving factors between medical students who have migraine and medical students who have risk to be migraine and to study levels of impact from migraine. Method : A Cross-sectional descriptive study was conducted in 2019 in Naresuan University. The data were collected by using self-administered questionnaires which included general charateristics, the ID MigraineTM and Thai-Migraine Disability Assessments test (Thai-MIDAS). The collected data were analyzed by using computer program. Results : In this study (n=362), the prevalence of migraine in medical students was 10.2% (n=37). Students who have a positive family history of migraine were more likely to have migraine than the students who have not (OR=2.66, 95% CI: 1.05-6.74, p<0.05). The most trigger factor of migraine was stress from studying (n=31, 83.78%). Coffee, sudden change in temperature, bright light and menstrual cycle were trigger factors significantly (p=0.037, 0.042, <0.001, 0.017 respectively). The most relieving factor of migraine was rest when migraine attack (n=31, 83.8%). Being in dark quite room, cold or hot pack on the head and neck were relieving factors significantly (p=0.011, 0.030, 0.008 respectively). Almost students who have migraine (n=13, 35.1%) and risk of migraine (n=90, 63.4%) were both little or none level of impact from migraine. Conclusion : Migraine is common in medical students at Naresuan University. The migraine’s symptoms affect to daily activities and learning. Studying the trigger factors and relieving factors in this study can apply for preventing the effect of migraine in medical students.